2017
DOI: 10.1080/17469899.2017.1276444
|View full text |Cite
|
Sign up to set email alerts
|

Dysthyroid optic neuropathy: update on pathogenesis, diagnosis, and management

Abstract: Introduction Dysthyroid optic neuropathy (DON) is a severe manifestation of thyroid eye disease (TED) that can result in permanent vision loss. Management is complex, multidisciplinary, and involves medical and/or surgical therapies. This review describes current concepts in the epidemiology, pathophysiology, diagnosis, and treatment of DON. Areas covered An extensive review of the literature was performed to detail current concepts on the diagnosis and management of DON. This includes utilization of various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
112
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 111 publications
2
112
0
5
Order By: Relevance
“…4 The compression may directly stretch the optic nerve on one hand and reduce the blood flow in short posterior ciliary and peripapillary retinal arteries on the other. 5,6 A report showed that superior ophthalmic vein blood flow velocity was significantly decreased in DON eyes, which implies that the abnormal hemodynamic state may participate in the development of DON. 7 Optical coherence tomography angiography (OCT-A) is a noninvasive technique capable of qualitatively and quantitatively evaluating the retinal and choroidal perfusion.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4 The compression may directly stretch the optic nerve on one hand and reduce the blood flow in short posterior ciliary and peripapillary retinal arteries on the other. 5,6 A report showed that superior ophthalmic vein blood flow velocity was significantly decreased in DON eyes, which implies that the abnormal hemodynamic state may participate in the development of DON. 7 Optical coherence tomography angiography (OCT-A) is a noninvasive technique capable of qualitatively and quantitatively evaluating the retinal and choroidal perfusion.…”
mentioning
confidence: 99%
“…19 The mechanism underlying DON appears to be multifactorial, and vascular insufficiency might be an important factor as in other optic neuropathies. 5,6 With the emergence of OCT-A, it is feasible to figure out the correlation between microvascular perfusion and the development of DON. A recent OCT-A study investigating the retinal vessel changes in active TAO eyes initiated the exploration to the contribution of intraocular blood flow in the development of TAO.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Visual field testing or visual evoked potentials were not tested for diagnosing DON in our patients. Visual loss is considered a late sign of DON, while color desaturation is an early sign [14]. Prior to rituximab, the first case developed visual decline and loss of color vision, while the second case had visual loss and a relative afferent papillary defect, indicating DON.…”
Section: Discussionmentioning
confidence: 99%
“…Optic neuropathy is a rare and severe complication of thyroid eye disease (TED), comprising four to eight per cent of all the complications that may manifest due to compression of the optic nerve by hypertrophy of the extraocular muscles, inflammation or compromised blood supply to the optic nerve. 1 Dysthyroid optic neuropathy appears later in the progression of TED and is rarely the presenting feature. Herein is presented a case of 60-year-old female who initially presented with acute painless unilateral diminution of vision, later diagnosed with TED and compressive optic neuropathy.…”
mentioning
confidence: 99%